Armed Oncolytic Adenoviruses and Polymer-shielded Nanocomplex for Systemic Delivery - Yoon, A-Rum; W. Kim, Sung; Yun, Chae-Ok (Current Cancer Therapy Reviews, 2015)
Oncolytic adenoviruses (Ad) that selectively replicate in cancer cells are emerging as a promising new modality for cancer treatment. The most attractive feature of oncolytic Ad is its ability to destroy cancer cells through a distinctive and unique function in which the virus selectively replicates and destroys tumors by cell lysis, a function that no anti-cancer drugs can mimic. Moreover, coupling the lytic function of oncolytic Ad with virus- mediated expression of therapeutic gene, termed “armed oncolytic Ad”, has been exceedingly promising in preclinical settings. However, systemic delivery of oncolytic Ad inevitably induces antiviral immune responses and nonspecific uptake to the liver due to Ad’s native tropism, resulting in short blood retention time, low therapeutic efficacy, and hepatotoxicity. Therefore, alternative strategies are required to enhance delivery of oncolytic Ad to targeted tumor tissues. To this end, surface modification of Ad by chemical and genetic engineering has been extensively studied. Surface modification can be categorized into two major subsets which are physical modification and chemical modification, resulting in alteration of Ad’s native tropism and enhancement of therapeutic efficacy and safety on systemic delivery of oncolytic Ad. These attributes make hybrid delivery system, which combines viral and non-viral carrier, a promising strategy for cancer gene therapy as each carrier’s strengths contribute to synergistic enhancement in delivery and therapeutic efficacy. Here, we describe various strategies currently being applied to maximize the therapeutic efficacy of oncolytic Ad. We also discuss advances in the integration of viral and non-viral nanomaterials aimed to overcome the limited clinical application of conventional Ads which will enable effective treatment of disseminated tumors via systemic injection.
Keywords: Active targeting